RISE: International Sustainability Invention, Innovation and Design Showcase (ISIIDS 2022) / Dr Emi Normalina Omar, Assoc. Prof. Dr Siti Noorsuriani Ma'on and Dr Nur Atiqah Rochin Demong - Omar, Emi Normalina; Ma'on, Siti Noorsuriani; Rochin Demong, Nur Atiqah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Recently, the Faculty of Business and Management, UiTM Cawangan Selangor, Puncak Alam Campus, organized an International Sustainability Invention, Innovation, and Design Showcase (ISIIDS2022) on March 20th, 2022. The "International Sustainability Invention, Innovation and Design Showcase'' (ISIIDS 2022) programme was designed to provide opportunities and exposure and highlight the use and application of inventions in a sustainable environment.